Analysis of The Employee Placement Based on Islamic Perspective: Case Study on Non – Academic Staff of University of Darussalam Gontor - Lathiefa Rusli; Abdul Aziz Husni Mubarok (Al Tijarah, 2021)
Human Resources are a necessity in running of the organization. The crucial and strategic role in its implementation should be considered on quality of human resources, one of which is the education institution of the University Darussalam Gontor (UNIDA Gontor) Ponorogo which upholds Islamic values. This study aims to determine how the implementation of the employee placement application, and whether the application of employee placement at the University of Darussalam Gontor is complied on Islamic Perspective or not on non-academic staff UNIDA Gontor. This research uses qualitative methods with data collection based on observation, interviews and documentation. The results of this study indicate that the application for employee placement on non-academic staff at UNIDA Gontor is in application with the procedures of resource management, such as job analysis, recruitment, selection and placement. Thus, the placement process at UNIDA Gontor is in complied with an Islamic perspective by upholding openness, justice, neatness, systematic and based on the results of deliberation.